A Quantitative Analysis of the Mass Media Coverage of Genomics Medicine in China: A Call for Science Journalism in the Developing World - Zhao, Feifei (Mary Ann Liebert, Inc., 2014)
Science journalism is a previously neglected but rapidly growing area of scholarship in postgenomics medicine and socio-technical studies of knowledge-based innovations. Science journalism can help evaluate the quantity and quality of information flux between traditional scientific expert communities and the broader public, for example, in personalized medicine education. Newspapers can play a crucial role in science and health communication, and more importantly, in framing public engagement. However, research on the role of newspaper coverage of genomics-related articles has not been readily available in resource-limited settings. As genomics is rapidly expanding worldwide, this gap in newspaper reportage in China is therefore an important issue. In order to bridge this gap, we investigated the coverage of genomics medicine in eight major Chinese national newspapers, using the China Core Newspapers Full-text Database (CCND) and articles in scientific journals in PubMed from 2000 to 2011. Coverage of genomics medicine in these eight official government Chinese newspapers has remained low, with only 12 articles published per newspaper per year between 2000 and 2011. Between 2000 and 2011, over a 40-fold difference was observed in the number of genomics medicine-related articles in PubMed, as compared to that in newspapers. The numbers of genomics-related articles among the eight major newspapers from 2000 to 2011 were significantly different (p=0.001). Commentary/mini reviews and articles about gene therapy for specific diseases were most frequently published in 2006 and 2011. In parallel, we observed that “cancer gene therapy,” “new susceptibility gene locus,” and “gene technology revolution” were the top three thematic strands addressed in the newspapers, even though their volume remained low. This study reports on the under-representation of newspaper coverage of genomics medicine in China, despite the vast growth of scientific articles in journals in this knowledge domain. This underscores the need to enhance collaboration between scientists, medical professionals, and journalists as an important strand of overall communications efforts in disseminating genomic medicine knowledge to larger audiences. Yet a substantive question remains to be examined: would traditional journalism, alone, be adequate to address the advances and challenges in genomics medicine in the media? Conversely, should we invest in science journalism programs as a subspecialty in biomedicine so scientists and clinicians acquire the twin scholarship of science/clinical medicine and journalism in their formative education?